2006
DOI: 10.1002/ajp.20315
|View full text |Cite
|
Sign up to set email alerts
|

Female social relationships in a captive group of Campbell's monkeys (Cercopithecus campbelli campbelli)

Abstract: A study group of Campbell's monkeys (Cercopithecus c. campbelli) provided data on affiliative and agonistic relationships between females. Over a period of two years (involving 111 hr), we conducted observations of a captive group which had a composition similar to wild groups. We were able to identify a monitor-adjust social system with frequent affiliative interactions, directed gazing and avoidances rather than aggressive acts. We described long-term differentiated affiliative bonds: adult females interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…In forest guenons, the single adult male of the group mainly vocalizes in response to predators and other significant external disturbances (5,48,53). Females are vocally active in social situations (44)(45)(46) and to predators to which they produce a diverse alarm call repertoire that encodes information about predator type and level of threat (47).…”
Section: Discussionmentioning
confidence: 99%
“…In forest guenons, the single adult male of the group mainly vocalizes in response to predators and other significant external disturbances (5,48,53). Females are vocally active in social situations (44)(45)(46) and to predators to which they produce a diverse alarm call repertoire that encodes information about predator type and level of threat (47).…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, researchers evaluated interactions among all group members, not just adult females. In Campbell's monkeys (Cercopithecus campbelli), there were more frequent affiliative interactions within each of two all-female matrilines (either a set of sisters, or a mother and multiple daughters) than there were between them [Lemasson et al, 2006]. The measure of affiliation included both grooming and proximity measures.…”
Section: Kin Bias In Grooming and Spatial Associationmentioning
confidence: 99%
“…Our general predic-tions were that the monkeys would select anti-predator strategies suitable to the forest habitat, take into account the different predator types and their associated hunting techniques, the momentary degree of threat, as well as their own vulnerability. In particular, based on the sexual dimorphism and previously described sex differences in guenon behaviour (Gautier & GautierHion, 1977;Lemasson et al, 2006), we predicted that the single male would play a more active role in predator defence.…”
Section: Introductionmentioning
confidence: 97%
“…The species is interesting because many of the variables discussed before have relevance, such as a dense forest habitat with high degree of arboreal locomotion (Mc Graw, 1996), different types of natural predators (Jenny & Zuberbühler, 2005;Shultz & Thomsett, 2007), complex social life (Lemasson et al, 2006;Buzzard & Eckardt, 2007) and sexual dimorphism (males, 5.5 kg; females, 3.5 kg: Glenn & Bensen, 1998). Males and females also differ in terms of their vocal behaviour (Zuberbühler, 2001;Ouattara et al, 2009 and data not shown).…”
Section: Introductionmentioning
confidence: 99%